HUBUNGAN PERAN SUAMI DENGAN ADAPTASI PSIKOLOGI IBU NIFAS PADA FASE TAKING HOLD DI PUSKESMAS DUONO - Fure, Elsianty; Sri Purwanti, Anik (NHM PRESS, 2024)
Background: The husband's role in supporting the psychological adaptation of postpartum mothers during the taking hold phase is an important aspect in postnatal care at the Duono Community Health Center. This study aims to explore the relationship between the husband's role and the psychological adaptation of postpartum mothers during the taking hold phase. Objective: This study aims to determine the extent to which the husband's role contributes to the psychological adaptation of postpartum mothers during the taking hold phase at the Duono Community Health Center. Method: This study used a cross-sectional design with a sample of 17 pregnant women selected by purposive sampling of postpartum mothers who visited the Duono Community Health Center. Data was collected through a questionnaire that measured the role of the husband and the psychological adaptation of postpartum mothers during the taking hold phase. Results: Data analysis shows that there is a positive relationship between the husband's active role and the psychological adaptation of postpartum mothers in the taking hold phase (p < 0.05). Conclusion: This study concludes that the husband's role has a significant impact on the psychological adaptation of postpartum mothers during the taking hold phase at the Duono Community Health Center. The support provided by the husband can help reduce stress and improve the psychological well-being of postpartum mothers. Increasing awareness and the active role of husbands in postnatal care needs to be strengthened in clinical practice at Community Health Centers to improve holistic care for postpartum mothers.